From diversity to disease: unravelling the role of enteric glial cells - Santhosh, Sneha; Zanoletti, Lisa; Stamp, Lincon A.; Hao, Marlene M.; Matteoli, Gianluca (Frontiers in Immunology, 2024)
Enteric glial cells (EGCs) are an essential component of the enteric nervous system (ENS) and play key roles in gastrointestinal development, homeostasis, and disease. Derived from neural crest cells, EGCs undergo complex differentiation processes regulated by various signaling pathways. Being among the most dynamic cells of the digestive system, EGCs react to cues in their surrounding microenvironment and communicate with various cell types and systems within the gut. Morphological studies and recent single cell RNA sequencing studies have unveiled heterogeneity among EGC populations with implications for regional functions and roles in diseases. In gastrointestinal disorders, including inflammatory bowel disease (IBD), infections and cancer, EGCs modulate neuroplasticity, immune responses and tumorigenesis. Recent evidence suggests that EGCs respond plastically to the microenvironmental cues, adapting their phenotype and functions in disease states and taking on a crucial role. They exhibit molecular abnormalities and altered communication with other intestinal cell types, underscoring their therapeutic potential as targets. This review delves into the multifaceted roles of EGCs, particularly emphasizing their interactions with various cell types in the gut and their significant contributions to gastrointestinal disorders. Understanding the complex roles of EGCs in gastrointestinal physiology and pathology will be crucial for the development of novel therapeutic strategies for gastrointestinal disorders.